Pengaruh Pengemasan dan Lama Penyimpanan Terhadap Karakteristik Kimia dan Fisik Pisang Tongka Langit (Musa troglodytarum L.) - Palijama, Syane; Ega, La (Universitas Pattimura, 2024)
Tongka langit banana (Musa troglodytarum L.) is a climacteric fruit and requires good post-harvest handling to reduce yield losses before consumption. Various factors can cause degradation and post-harvest losses, so applying proper post-harvest handling increases shelf life by delaying ripening, reducing respiration rates, and reducing storage losses. This study examines and analyzes the effect of vacuum packaging and storage time on changes in physiological and physical characteristics of tongka langit banana fruit during storage. This study was designed using a complete randomized design. Factorial pattern. The variables measured were sugar content, total soluble solids (TSS), texture, and weight loss. Sugar content was measured by titration, total soluble solids were measured using a refractometer, texture was measured using a universal testing machine, and weight loss was measured by the weighing method. The results of the study showed that packaging affected the chemical and physical characteristics of tongka langit bananas, including total sugar content (10.71-11.24%), TSS (12.08-26.76%Brix), weight loss (8.79-10.72%) and texture (196.80-198.40 N/cm2). Storage time affected the chemical and physical characteristics of tongka langit bananas, including total sugar content (10.72-12.58%), TSS (24.36-27.22%Brix), weight loss (9.02-11.27%), and texture (164.40-168.20 N/cm2).